2020
DOI: 10.3390/molecules25153422
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bioavailability Evaluation of Celastrol-Encapsulated Silk Fibroin Nanoparticles Using an Optimized LC-MS/MS Method

Abstract: Celastrol (CL), a compound isolated from Tripterygium wilfordii, possesses various bioactivities such as antitumor, anti-inflammatory and anti-obesity effects. In previous studies, we developed CL-encapsulated silk fibroin nanoparticles (CL-SFNP) with satisfactory formulation properties and in vitro cancer cytotoxicity effect. For further in vivo oral bioavailability evaluation, in this study, a simple and reliable LC-MS/MS method was optimized and validated to determine CL concentration in rat plasma. The sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Supplementation of the culture medium with FF or FF‐derived EVs changes the gene expression profiles of oviductal epithelial cells. 17 These reports indicate that the FF flux into the oviduct regulates the cells surrounding the embryos. Consistently, the protein expression of oviductal fluids (OFs) ipsilateral to the ovulated ovary differs from those of the contralateral counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of the culture medium with FF or FF‐derived EVs changes the gene expression profiles of oviductal epithelial cells. 17 These reports indicate that the FF flux into the oviduct regulates the cells surrounding the embryos. Consistently, the protein expression of oviductal fluids (OFs) ipsilateral to the ovulated ovary differs from those of the contralateral counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the bioavailability of Tri, a variety of oral nano-vehicles have been explored, including phytosomes [ 20 , 38 ], silk fibroin nanoparticles [ 39 ], and lactosylated albumin nanoparticles [ 40 ]. Compared with silk fibroin nanoparticles and lactosylated albumin nanoparticles, the selenized PLN system developed by us resulted in higher blood drug concentrations, in addition to longer in vivo residence times.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional routes of administration, such as oral and intravenous, are not ideal for Cela delivery. For instance, a pharmacokinetic study done on rats demonstrated the mean oral absolute bioavailability after oral administration (3 mg/kg) was very low at 3.14% [ 55 ]. Even though bioavailability is not a concern in intravenous administration, Cela is associated with many side effects, including infertility, cardiotoxicity, hepatotoxicity, hematopoietic system toxicity, and nephrotoxicity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%